Robert’s Uterus, Rare Uterine Anomaly: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Roberts uterus is an extremely rare variety of congenital mullerian duct anomaly. It is also known as asymmetric septate uterus. The uterine septum is complete and fused with uterine wall on one side dividing the cavity into two: one non-communicating and another communicating with cervix. Regular menstrual flow occurs from the communicating cavity. At the same time, obstruction to menstrual flow in one cavity results in formation of hematometra, sometimes hematosalpinx and endometriosis. Presenting symptoms are severe dysmenorrhea and abdominal pain.Imaging modalities like three dimensional ultrasonography or magnetic resonance imaging are useful in diagnosing the mullerian duct anomaly. Traditionally the condition has been treated by laparotomy followed by complete excision of the obstructed one sided cavity. In recent years, incision of septum has been done by hysteroscopy, resulting in a uterine cavity with better reproductive outcome. Here presented the case of a 19 year old woman with Robert’s uterus. The imaging modalities failed to diagnose the case. The anomaly was explored by laparoscopy and hysteroscopy followed by laparotomy. The obstructed hemi-cavity had thick altered blood. It was obliterated following excision of endometrium. The woman was relieved of pain thereafter.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 125-129